Composite electrode active layer, electrode plate and secondary battery

By designing the composite electrode active layer in the secondary battery, combining heat-resistant polymers, thermally sensitive polymers and inorganic particles, the problem of poor safety and stability of the separator at high temperatures is solved, and low closed-pore temperature and high film breakage are achieved The balance of temperature significantly improves the high temperature safety of the battery.

CN119297255AActive Publication Date: 2025-01-10EVE POWER CO LTD

Patent Information

Application Number
CN202411692060.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-01-10
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

The existing secondary battery separators are difficult to have both low closed-cell temperature and high rupture temperature, resulting in poor safety and stability at high temperatures, and are prone to problems with internal short circuits and thermal runaways.

Method used

Design a composite electrode active layer, including a layer of active material and a composite insulating layer stacked in sequence, the composite insulating layer contains heat-resistant polymers, thermally sensitive polymers and inorganic particles. By optimizing the component proportion and structure, the composite insulating layer can be achieved. The combination of low closed-cell temperature and high film breaking temperature enhances the high-temperature safety of the battery.

Benefits of technology

It effectively prevents thermal runaway caused by film rupture at high temperatures, significantly improves the high-temperature safety and stability of the secondary battery, and avoids the occurrence of short circuits inside the electrodes, smoke, explosions and other accidents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005153718870000181
    Figure BDA0005153718870000181
  • Figure BDA0005153718870000191
    Figure BDA0005153718870000191
Patent Text Reader

Abstract

The invention provides a composite electrode active layer, an electrode plate and a secondary battery. The composite electrode active layer comprises an active material layer and a composite insulating layer which are stacked in sequence, wherein the composite insulating layer comprises inorganic particles, a heat-resistant polymer and a thermosensitive polymer; the weight ratio of the inorganic particles to the heat-resistant polymer to the thermosensitive polymer is (50-100): (1-10): (5-50); the melting temperature of the heat-resistant polymer is 180-450 DEG C; and the softening temperature of the thermosensitive polymer is 80-120 DEG C. According to the invention, the active layer of the composite electrode is designed, so that the composite electrode has low hole closing temperature and high membrane rupture temperature, and the porous structure and the high-temperature-resistant characteristic are further realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of secondary batteries, and in particular to a composite electrode active layer, an electrode sheet and a secondary battery. Background Art

[0002] In order to meet the growing demand for batteries, high-capacity and high-energy-density secondary batteries have also received more and more attention. Lithium-ion batteries and sodium-ion batteries, as mainstream products of secondary batteries, have been widely used in many fields such as new energy vehicles, wearable devices, and portable power supplies. As one of the commonly used components of secondary batteries at this stage, the diaphragm mainly plays the role of ion transmission and electronic isolation. The closed-pore temperature and membrane rupture temperature of the diaphragm are key technical indicators that characterize the safety of the diaphragm and even the safety of the battery cell. At present, the mass-produced diaphragm substrates are made of PE and PP materials. The closed-pore temperature of the PE diaphragm is ~130℃, and the closed-pore temperature of the PP diaphragm is ~150℃, which results in the diaphragm being unable to achieve timely closure to prevent the transmission of conductive ions when it is thermally abused. At the same time, the PE membrane rupture temperature is ~145℃, and the PP membrane rupture temperature is ~170℃, which further causes the diaphragm to rupture when the battery cell is thermally abused, the positive and negative electrodes are short-circuited, and safety accidents such as smoking and explosion occur. Therefore, the existing diaphragms cannot truly be compatible with low closed-pore temperatures and high membrane rupture temperatures.

[0003] In the safety design of secondary batteries, the problem of short circuit inside the electrode is particularly important. The internal short circuit of the battery will cause the internal temperature of the battery to rise rapidly, and in severe cases, it will cause thermal runaway of the battery. Therefore, how to effectively prevent the internal short circuit of the electrode is one of the key issues that need to be solved in the design of secondary batteries.

[0004] At present, the methods of preventing internal short circuit of electrodes are mainly divided into two categories: one is to add inorganic particles with thermal expansion and contraction properties to the active material layer. For example, Chinese patent CN103381436A discloses a composite electrode active material with thermal expansion and contraction properties. The active material is based on a positive electrode active material, and inorganic particles with thermal expansion and contraction properties are added to the positive electrode active material. The amount of inorganic particles added is 1-10% of the positive electrode active material; the inorganic particles are inorganic powders with thermal expansion and contraction properties. In the above patent technology, the amount of inorganic powder added is small, and the inorganic powder and the active material are not fully mixed. The inorganic powder is easy to form voids in the electrode material, thereby increasing the capacity loss of the active material and having a negative impact on the physical and electrochemical properties of the electrode material. The other is to set an insulating layer on both sides of the active material layer. For example, Chinese patent CN101937953A discloses a positive electrode layer of a lithium ion battery, which includes a positive electrode active material layer, a binder layer disposed on both sides of the positive electrode active material layer, and an insulating layer disposed on the side of the positive electrode active material layer away from the binder layer; the insulating layer has a thermal expansion coefficient of less than 4×10-5 / ℃ low thermal expansion coefficient insulation layer. In order to ensure that the thermal expansion coefficient of the insulation layer is less than 4×10 -5 / ℃, the material of the insulating layer is ceramic material, the price of ceramic material is relatively high, and the processing technology of ceramic material is complicated and the production cost is high.

[0005] Based on this, how to provide a composite electrode active layer that has both low closed-pore temperature and high membrane rupture temperature, so that it can play the role of ion transmission and electron isolation while improving the safety and stability of the corresponding secondary battery at high temperature, is one of the important technical problems that need to be solved in this field. Summary of the invention

[0006] The main purpose of the present invention is to provide a composite electrode active layer, an electrode sheet and a secondary battery to solve the problem that the secondary battery separator in the prior art is difficult to have both a low closed-pore temperature and a high membrane rupture temperature, which leads to poor safety and stability of the secondary battery at high temperatures.

[0007] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a composite electrode active layer, which comprises an active material layer and a composite insulating layer stacked in sequence, wherein the composite insulating layer comprises a heat-resistant polymer, a thermosensitive polymer and inorganic particles; the weight ratio of the inorganic particles, the heat-resistant polymer and the thermosensitive polymer is (50-100): (1-10): (5-50); the melting temperature of the heat-resistant polymer is 180°C-450°C; the softening temperature of the thermosensitive polymer is 80°C-120°C.

[0008] Furthermore, the weight ratio of the inorganic particles, the heat-resistant polymer and the thermosensitive polymer is (65-85):(3-5):(10-30).

[0009] Furthermore, the heat-resistant polymer is selected from one or more of polyacrylate polymers, polyimide polymers and amide polymers; preferably, the heat-resistant polymer is selected from one or more of poly(m-phenylene isophthalamide), polyethylene terephthalate and poly(bismaleimide).

[0010] Furthermore, the thermosensitive polymer is selected from one or more of polyol polymers and polyvinyl alcohol polymers; preferably, the thermosensitive polymer is polyethylene glycol and / or polyvinyl alcohol.

[0011] Furthermore, the D50 of the inorganic particles is 0.1μm~6.0μm, and (D90-D10) / D50 is 0.5~3.0; preferably, the inorganic particles are selected from one or more of boehmite, Al2O3, BaTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, SiO2, Y2O3, SiC and TiO2; more preferably, the inorganic particles are BaTiO3 and TiO2, and the weight ratio of BaTiO3 and TiO2 is (0.1~10):1.

[0012] Furthermore, the thickness of the composite insulating layer is 4 μm to 20 μm; preferably, the ratio of the thickness of the composite insulating layer to the active material layer is (0.01 to 0.5): 1; preferably, the active material layer is a positive electrode material active layer and / or a negative electrode active material layer; more preferably, the positive electrode material is selected from one or more of iron phosphate, manganese iron phosphate and nickel-cobalt-manganese ternary material; and / or, the negative electrode material is selected from one or more of graphite, silicon and silicon-carbon composite materials.

[0013] Furthermore, the inorganic particles are BaTiO3 and TiO2, and the weight ratio of the BaTiO3 and the TiO2 is (0.4-0.5):1; and / or, the heat-resistant polymer is poly(m-phenylene isophthalamide) and polyethylene terephthalate, and the weight ratio of poly(m-phenylene isophthalamide) and polyethylene terephthalate is 1:(0.8-1.2); and / or, the thermosensitive polymer is polyethylene glycol and polyvinyl alcohol, and the weight ratio of polyethylene glycol and polyvinyl alcohol is 1:(1.8-2.0).

[0014] The second aspect of the present invention provides an electrode sheet, comprising a current collector and an electrode active layer arranged on at least one side surface of the current collector, wherein the electrode active layer is the above-mentioned composite electrode active layer, and the active material layer in the composite electrode active layer is arranged in contact with the current collector; preferably, the composite insulating layer is arranged on the side surface of the active material layer away from the current collector by a coating process, and the coating surface density of the composite insulating layer during coating is 15g / m 2 ~45g / m 2 ; The electrode sheet is a negative electrode sheet and / or a positive electrode sheet.

[0015] Furthermore, the electrode sheet is a positive electrode sheet, the current collector is a positive current collector, the active material layer is a positive material active layer, the positive material active layer is arranged on the positive current collector through a coating process, and the coating surface density of the positive material active layer during coating is 100g / m 2 ~400g / m 2; and / or, the electrode sheet is a negative electrode sheet, the current collector is a negative current collector, the active material layer is a negative material active layer, the negative material active layer is disposed on the negative current collector by a coating process, and the coating surface density of the negative material active layer during coating is 40 g / m 2 ~200g / m 2 .

[0016] A third aspect of the present invention provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the positive electrode sheet is the above-mentioned positive electrode sheet; and / or the negative electrode sheet is the above-mentioned negative electrode sheet.

[0017] By applying the technical solution of the present invention, the active layer of the composite electrode is designed to achieve both a low closed-cell temperature and a high membrane rupture temperature, thereby achieving a porous structure and high temperature resistance, solving the problem of thermal runaway of secondary batteries caused by membrane rupture due to high temperature in traditional diaphragms, and also preventing the occurrence of thermal runaway, thereby significantly improving the high-temperature safety of the corresponding secondary batteries. DETAILED DESCRIPTION

[0018] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0019] As described in the background art, the secondary battery separator in the prior art has the problem of difficulty in having both a low closed-cell temperature and a high membrane rupture temperature, which leads to the problem of poor safety and stability of the secondary battery at high temperatures. In order to solve the above technical problems, the first aspect of the present invention provides a composite electrode active layer, which includes an active material layer and a composite insulating layer stacked in sequence, and the composite insulating layer includes a heat-resistant polymer, a thermosensitive polymer and inorganic particles; the weight ratio of the inorganic particles, the heat-resistant polymer and the thermosensitive polymer is (50-100): (1-10): (5-50); the melting temperature of the heat-resistant polymer is 180°C-450°C; the softening temperature of the thermosensitive polymer is 80°C-120°C.

[0020] The present invention achieves both low pore closing temperature and high membrane rupture temperature by designing the composite electrode active layer, thereby obtaining a composite electrode active layer with a porous structure and high temperature resistance.

[0021] Specifically, a porous composite insulating coating is provided on the surface of the active material layer. Compared with the traditional diaphragm, it can realize the effective transmission of conductive ions while isolating the direct contact between the positive and negative electrode main materials. The composite insulating layer provided by the present invention adopts a heat-resistant polymer, which is used as a high-melting-point adhesive, thereby obtaining high-temperature resistance and solving the problem of thermal runaway caused by high temperature in the traditional diaphragm. The addition of inorganic particles improves the mechanical strength and electrochemical stability of the composite insulating layer, and further optimizes the comprehensive performance of the battery. At the same time, the above-mentioned composite insulating layer provided by the present invention also includes a thermosensitive polymer, and its melting temperature significantly optimizes the closed-cell temperature of the obtained composite insulating layer. That is, when applied to secondary batteries, the above-mentioned thermosensitive polymer with a softening temperature of 80°C to 120°C can achieve a melting state within this temperature range, block the porous structure in the coating, hinder the transfer of conductive ions at high temperatures, and rapidly increase its high-temperature internal resistance, thereby preventing the occurrence of thermal runaway of the battery.

[0022] In particular, in addition to the functional gains brought by each of the three components, the dosage coordination relationship of the three is indispensable. On this basis, the present invention strictly controls the dosage ratio of the three within the above range, so that the inorganic particles, heat-resistant polymers and thermosensitive polymers can be better coordinated, thereby significantly optimizing the porous structure of the obtained composite insulating layer, while ensuring that it can have a low closed-cell temperature and a high film-breaking temperature, and finally obtaining a high-temperature resistant composite electrode active layer.

[0023] In several preferred embodiments, the weight ratio of inorganic particles, heat-resistant polymer and thermosensitive polymer is (65-85): (3-5): (10-30). Based on the above content, this further optimized usage ratio can not only improve the stability and mechanical strength of the composite insulating layer under normal working conditions, but also respond more quickly when the battery is overheated, effectively preventing the transmission of conductive ions, and further improving the safety and reliability of the battery.

[0024] The heat-resistant polymer in the present invention is preferably selected from one or more of polyacrylate polymers, polyimide polymers and amide polymers, and more preferably selected from one or more of poly(m-phenylene isophthalamide), polyethylene terephthalate and poly(bismaleimide). The above-mentioned heat-resistant polymers have better heat resistance and chemical stability, and can more effectively improve the thermal stability and electrochemical stability of the composite insulating layer.

[0025] In order to obtain a composite insulating layer with stronger mechanical properties on the basis of a high melting temperature, it is more preferred that the heat-resistant polymer is poly(m-phenylene isophthalamide) and polyethylene terephthalate, and the weight ratio of poly(m-phenylene isophthalamide) to polyethylene terephthalate is 1:(0.8-1.2). The inventors have found through a large number of experiments that this combination can more fully utilize the complementary properties of the two heat-resistant polymers, thereby providing the obtained composite insulating layer with higher heat resistance and mechanical strength, thereby more significantly optimizing the high-temperature safety of the corresponding secondary battery.

[0026] The thermosensitive polymer in the present invention is preferably selected from one or more of polyol polymers and polyvinyl alcohol polymers, and more preferably polyethylene glycol and / or polyacrylic acid. Compared with other polymers in the art with softening temperatures in the temperature range of 80°C to 120°C, the thermosensitive polymer has better thermal sensitivity, can respond more quickly when the battery in which it is located overheats, prevents the transmission of conductive ions therein, plays a more effective self-insurance role, and ultimately significantly reduces the possibility of short circuits inside the battery.

[0027] Furthermore, after a large number of experiments, the inventors preferred the thermosensitive polymers to be polyethylene glycol and polyvinyl alcohol, and the weight ratio of polyethylene glycol to polyvinyl alcohol was 1:(1.8-2.0), so as to provide the obtained composite insulating layer with superior thermosensitive properties while further balancing and improving its chemical stability, and ultimately making the corresponding secondary battery exhibit better high-temperature safety.

[0028] Furthermore, in order to more significantly optimize the porous structure of the obtained composite insulating layer, thereby obtaining an electrode sheet with higher mechanical strength and greater stability, the D50 of the inorganic particles is preferably 0.1 μm to 6.0 μm, and (D90-D10) / D50 is 0.5 to 3.0.

[0029] In several preferred embodiments, the inorganic particles are selected from one or more of boehmite (whose molecular formula is Al(OH)3), Al2O3, BaTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, SiO2, Y2O3, SiC and TiO2. The above inorganic particles can not only improve the mechanical strength and electrochemical stability of the composite insulating layer, but also make the resulting composite insulating layer and the corresponding secondary battery have higher thermal stability. After a large number of experiments, the inventors further preferred that the inorganic particles are BaTiO3 and TiO2, and the weight ratio of BaTiO3 to TiO2 is (0.1-10):1, more preferably (0.4-0.5):1. The combination of BaTiO3 and TiO2 in the above dosage ratio can provide excellent electrochemical performance and thermal stability, and when the secondary battery in which it is located is overheated, it can absorb heat more effectively, further improving the safety of the battery. In addition, BaTiO3 has a positive temperature coefficient effect, and its resistance value increases with rising temperature, which can further increase the internal resistance of the battery under high temperature conditions and prevent thermal runaway; it also has good chemical stability and is not easy to decompose and collapse at high temperatures, ensuring the structural stability of the insulating layer; the two can be used in combination to achieve a synergistic effect.

[0030] Furthermore, in order to better exert the composite insulating layer's gain effect on the heat resistance of the composite electrode active layer and obtain an electrode sheet with better high temperature stability, the thickness of the composite insulating layer is preferably 4 μm to 20 μm. The preferred ratio of the thickness of the composite insulating layer to the active material layer is (0.01 to 0.5):1, which can better balance thermal stability and electrochemical performance, so that the electrode sheet in which it is located has a higher energy density while maintaining good thermal stability.

[0031] Preferably, the active material layer is a positive electrode material active layer and / or a negative electrode active material layer; more preferably, the positive electrode material is selected from one or more of iron phosphate, manganese iron phosphate and nickel-cobalt-manganese ternary material; specifically, when the secondary battery is a lithium-ion battery, the positive electrode material may be LFP, LMFP and NCM. And / or, the negative electrode material is selected from one or more of graphite, silicon and silicon-carbon composite materials.

[0032] In several preferred embodiments, the inorganic particles are BaTiO3 and TiO2, and the weight ratio of the BaTiO3 and the TiO2 is (0.4-0.5):1; and / or, the heat-resistant polymer is poly(m-phenylene isophthalamide) and polyethylene terephthalate, and the weight ratio of poly(m-phenylene isophthalamide) and polyethylene terephthalate is 1:(0.8-1.2); and / or, the thermosensitive polymer is polyethylene glycol and polyvinyl alcohol, and the weight ratio of polyethylene glycol and polyvinyl alcohol is 1:(1.8-2.0). The inventor has optimized the dosage of the components of the composite insulating layer through a large number of experiments and obtained the above-mentioned specific scheme. When the composite insulating layer formed by the above scheme forms a composite electrode active layer together with the active material layer and is applied to a secondary battery, the resulting secondary battery can exhibit higher high-temperature safety.

[0033] The second aspect of the present invention provides an electrode sheet, comprising a current collector and an electrode active layer arranged on at least one side surface of the current collector, wherein the electrode active layer is the above-mentioned composite electrode active layer, and the active material layer in the composite electrode active layer is arranged in contact with the current collector; preferably, the composite insulating layer is arranged on the side surface of the active material layer away from the current collector by a coating process, and the coating surface density of the composite insulating layer during coating is 15g / m 2 ~45g / m 2 The electrode sheet is a negative electrode sheet and / or a positive electrode sheet. The negative electrode sheet and / or the positive electrode sheet obtained by the present invention and comprising the composite electrode active layer has excellent high temperature resistance, thereby showing higher safety and stability at high temperatures. In particular, in the preparation process of the electrode sheet, the composite insulating layer is coated with a surface density of 15g / m 2 ~45g / m 2 The coating is formed in a coating manner, which can form a closer bond between it and the active material layer, thereby significantly improving the high-temperature thermal stability and structural stability of the obtained negative electrode sheet and / or positive electrode sheet.

[0034] As for the formation of the positive electrode material active layer and / or the negative electrode material active layer, in order to make it better cooperate with the subsequently coated composite insulating layer during the preparation process to form an electrode sheet with higher electrochemical performance, high temperature resistance and structural stability, in several preferred embodiments: the electrode sheet is a positive electrode sheet, the current collector is a positive current collector, the active material layer is a positive electrode material active layer, the positive electrode material active layer is arranged on the positive current collector through a coating process, and the coating surface density of the positive electrode material active layer during coating is 100g / m 2 ~400g / m 2; and / or, the electrode sheet is a negative electrode sheet, the current collector is a negative current collector, the active material layer is a negative material active layer, the negative material active layer is disposed on the negative current collector by a coating process, and the coating surface density of the negative material active layer during coating is 40 g / m 2 ~200g / m 2 .

[0035] Specifically, in actual production applications, the coating process can be selected from gravure coating, transfer coating, extrusion coating, and blade coating, etc. Meanwhile, in the coating process, one or more of DI water (Deionized Water), N-Methyl-2-pyrrolidone (NMP), and dimethylformamide (DMF) can be used as a dispersant for the mixed slurry used for coating.

[0036] The third aspect of the present invention provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the positive electrode sheet is the positive electrode sheet described above; and / or the negative electrode sheet is the negative electrode sheet described above. The composite electrode active layer obtained by the present invention, when combined with a current collector to obtain an electrode sheet and applied to a secondary battery, effectively solves the problem of thermal runaway of secondary batteries caused by membrane rupture due to high temperature caused by traditional diaphragms, and also prevents the occurrence of thermal runaway, significantly improving the high temperature safety of the corresponding secondary battery.

[0037] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0038] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0039] Example 1

[0040] A method for preparing a composite electrode active layer:

[0041] (1) boehmite is selected as inorganic particles, poly(m-phenylene isophthalamide) is selected as a heat-resistant polymer, polyethylene glycol (PEG) is selected as a thermosensitive polymer, and the ingredients are prepared according to a weight ratio of inorganic particles: heat-resistant polymer: thermosensitive polymer of 65:5:30, and NMP is used as a dispersant to obtain a composite insulation layer mixed slurry;

[0042] Among them, the D50 of boehmite is 0.1 μm, and (D90-D10) / D50 is 3; the melting temperature of the heat-resistant polymer poly(m-phenylene isophthalamide) is 270°C; and the softening temperature of the thermosensitive polymer PEG is 85°C.

[0043] (2) LFP is used as a positive electrode active material, PVDF is used as a binder, conductive carbon black and carbon nanotubes (CNT) are used together as conductive agents, and the ingredients are prepared according to a weight ratio of positive electrode active material: conductive carbon black: CNT: PVDF of 95:0.5:0.5:2.0, and NMP is used as a dispersant to obtain a positive electrode mixed slurry.

[0044] (3) Using graphite as a negative electrode active material, SBR as a binder, CMC as a thickener, and conductive carbon black as a conductive agent, the ingredients are prepared according to a weight ratio of negative electrode active material: conductive carbon black: SBR: CMC of 96:1:2:1, and deionized water is used as a dispersant to obtain a negative electrode mixed slurry.

[0045] (4) Aluminum foil was used as the positive electrode current collector at a pressure of 100 g / m 2 The obtained positive electrode mixed slurry was coated on both sides of the positive electrode current collector, and after rolling, a positive electrode material active layer with a thickness of 55 μm was formed on both sides; copper foil was used as the negative electrode current collector at a coating density of 40 g / m 2 The obtained negative electrode mixed slurry is coated on both sides of the negative electrode current collector with a coating surface density of, and after rolling, both sides of the surface form a negative electrode material active layer with a thickness of 30 μm.

[0046] (5) According to 15g / m 2 The obtained composite insulating layer mixed slurry is coated on two positive electrode material active layers and two negative electrode material active layers respectively to form composite electrode active layers, wherein the thickness of the composite insulating layer is 4 μm.

[0047] The thickness ratio of the formed composite insulating layer to the active layer of the negative electrode material is 0.133:1, and the thickness ratio of the formed composite insulating layer to the active layer of the positive electrode material is 0.08:1.

[0048] Example 2

[0049] A method for preparing a composite electrode active layer:

[0050] (1) Al2O3 is selected as inorganic particles, polyethylene terephthalate is selected as a heat-resistant polymer, polyvinyl alcohol is selected as a thermosensitive polymer, and the ingredients are prepared according to a weight ratio of inorganic particles: heat-resistant polymer: thermosensitive polymer of 85:5:10, and DI water is used as a dispersant to obtain a composite insulation layer mixed slurry;

[0051] Among them, the D50 of Al2O3 is 6μm, (D90-D10) / D50 is 0.5; the melting temperature of the heat-resistant polymer polyethylene terephthalate is 260℃; and the softening temperature of the heat-sensitive polymer polyvinyl alcohol is 96℃.

[0052] (2) Referring to the conditions in Example 1, a positive electrode mixed slurry was obtained.

[0053] (3) Referring to the conditions in Example 1, a negative electrode mixed slurry was obtained.

[0054] (4) Aluminum foil was used as the positive electrode current collector at 400 g / m 2 The obtained positive electrode mixed slurry was coated on both sides of the positive electrode current collector, and after rolling, a positive electrode material active layer with a thickness of 210 μm was formed on both sides of the positive electrode current collector; copper foil was used as the negative electrode current collector at a coating density of 200 g / m 2 The obtained negative electrode mixed slurry was coated on both sides of the negative electrode current collector with a coating surface density of, and after rolling, both sides of the negative electrode material active layer with a thickness of 130 μm was formed.

[0055] (5) According to 45g / m 2 The obtained composite insulating layer mixed slurry is coated on two positive electrode material active layers and two negative electrode material active layers respectively to form composite electrode active layers, wherein the thickness of the composite insulating layer is 20 μm.

[0056] The thickness ratio of the formed composite insulating layer to the active layer of the negative electrode material is 0.15:1, and the thickness ratio of the formed composite insulating layer to the active layer of the positive electrode material is 0.10:1.

[0057] Example 3

[0058] A method for preparing a composite electrode active layer:

[0059] (1) BaTiO3 and TiO2 (BaTiO3:TiO2=0.5:1, weight ratio) are selected as inorganic particles, a mixture of poly(m-phenylene isophthalamide) and polyethylene terephthalate is selected as a heat-resistant polymer (poly(m-phenylene isophthalamide) : polyethylene terephthalate=1:1, weight ratio), a mixture of poly(vinyl alcohol) and PEG is selected as a thermosensitive polymer (PEG:polyvinyl alcohol=1:2, weight ratio), and the ingredients are prepared according to the weight ratio of inorganic particles: heat-resistant polymer: thermosensitive polymer of 75:3:22, and DMF is used as a dispersant to obtain a composite insulating layer mixed slurry;

[0060] Among them, the D50 of BaTiO3 is 3μm, (D90-D10) / D50 is 1.5; the D50 of TiO2 is 1.2μm, (D90-D10) / D50 is 2.7; the melting temperature of the mixture formed by poly(m-phenylene isophthalamide) and polyethylene terephthalate is 264°C; the softening temperature of the mixture formed by poly(vinyl alcohol) and PEG is 89°C.

[0061] (2) Referring to the conditions in Example 1, a positive electrode mixed slurry was obtained.

[0062] (3) Referring to the conditions in Example 1, a negative electrode mixed slurry was obtained.

[0063] (4) Aluminum foil was used as the positive electrode current collector at 250 g / m 2 The obtained positive electrode mixed slurry was coated on both sides of the positive electrode current collector, and after rolling, a positive electrode material active layer with a thickness of 132 μm was formed on both sides of the positive electrode current collector; copper foil was used as the negative electrode current collector at a coating density of 120 g / m 2 The obtained negative electrode mixed slurry was coated on both sides of the negative electrode current collector with a coating surface density of, and after rolling, both sides of the negative electrode material active layer with a thickness of 78 μm was formed.

[0064] (5) According to 30g / m 2 The obtained composite insulating layer mixed slurry is coated on two positive electrode material active layers and two negative electrode material active layers respectively to form composite electrode active layers, wherein the thickness of the composite insulating layer is 12 μm.

[0065] The thickness ratio of the formed composite insulating layer to the active layer of the negative electrode material is 0.15:1, and the thickness ratio of the formed composite insulating layer to the active layer of the positive electrode material is 0.09:1.

[0066] Example 4

[0067] A method for preparing a composite electrode active layer:

[0068] The only difference between this embodiment and embodiment 1 is that the weight ratio of inorganic particles: heat-resistant polymer: thermosensitive polymer in step (1) is changed to 50:1:50.

[0069] Example 5

[0070] A method for preparing a composite electrode active layer:

[0071] The only difference between this embodiment and embodiment 1 is that the weight ratio of inorganic particles: heat-resistant polymer: thermosensitive polymer in step (1) is changed to 100:10:5.

[0072] Example 6

[0073] A method for preparing a composite electrode active layer:

[0074] The only difference between this embodiment and embodiment 1 is that the particle size distribution of the boehmite used is changed so that D50 is 0.05 μm and (D90-D10) / D50 is 4.0.

[0075] Example 7

[0076] A method for preparing a composite electrode active layer:

[0077] The only difference between this embodiment and embodiment 2 is that the particle size distribution of the Al2O3 used is changed so that its D50 is 8.0 μm and (D90-D10) / D50 is 0.3.

[0078] Example 8

[0079] A method for preparing a composite electrode active layer:

[0080] The only difference between this embodiment and embodiment 3 is that the usage ratio of BaTiO3 and TiO2 is changed to BaTiO3:TiO2=0.1.

[0081] Example 9

[0082] A method for preparing a composite electrode active layer:

[0083] The only difference between this embodiment and embodiment 3 is that the usage ratio of BaTiO3 and TiO2 is changed to BaTiO3:TiO2=10.

[0084] Example 10

[0085] A method for preparing a composite electrode active layer:

[0086] The only difference between this embodiment and embodiment 3 is that the weight ratio of the heat-resistant polymer poly(m-phenylene isophthalamide) to polyethylene terephthalate is changed to 1:0.5.

[0087] Embodiment 11

[0088] A method for preparing a composite electrode active layer:

[0089] The only difference between this embodiment and embodiment 3 is that the weight ratio of the heat-resistant polymer poly(m-phenylene isophthalamide) to polyethylene terephthalate is changed to 1:2.

[0090] Example 12

[0091] A method for preparing a composite electrode active layer:

[0092] The only difference between this embodiment and embodiment 3 is that the weight ratio of the thermosensitive polymer PEG to polyvinyl alcohol is changed to 1:1.

[0093] Example 13

[0094] A method for preparing a composite electrode active layer:

[0095] The only difference between this embodiment and embodiment 3 is that the weight ratio of the thermosensitive polymer PEG to polyvinyl alcohol is changed to 1:3.

[0096] Embodiment 14

[0097] A method for preparing a composite electrode active layer:

[0098] The difference between this embodiment and embodiment 3 is only in step (4) and step (5), specifically:

[0099] (4) Aluminum foil was used as the positive electrode current collector at 80 g / m 2 The obtained positive electrode mixed slurry was coated on both sides of the positive electrode current collector, and a positive electrode material active layer with a thickness of 350 μm was formed on both sides; copper foil was used as the negative electrode current collector at a coating density of 30 g / m 2 The obtained negative electrode mixed slurry is coated on both side surfaces of the negative electrode current collector with a coating surface density of, and a negative electrode material active layer with a thickness of 50 μm is formed on both side surfaces.

[0100] (5) According to 10g / m 2 The obtained composite insulating layer mixed slurry is coated on two positive electrode material active layers and two negative electrode material active layers respectively to form composite electrode active layers, wherein the thickness of the composite insulating layer is 30 μm.

[0101] The thickness ratio of the formed composite insulating layer to the active layer of the negative electrode material is 0.6:1, and the thickness ratio of the formed composite insulating layer to the active layer of the positive electrode material is 0.009:1.

[0102] Embodiment 15

[0103] A method for preparing a composite electrode active layer:

[0104] The difference between this embodiment and embodiment 3 is only in step (4) and step (5), specifically:

[0105] (4) Aluminum foil was used as the positive electrode current collector at 500 g / m 2 The obtained positive electrode mixed slurry was coated on both sides of the positive electrode current collector, and a positive electrode material active layer with a thickness of 350 μm was formed on both sides; copper foil was used as the negative electrode current collector at a coating density of 300 g / m 2The obtained negative electrode mixed slurry is coated on both side surfaces of the negative electrode collector with a coating surface density of, and a negative electrode material active layer with a thickness of 5 μm is formed on both side surfaces.

[0106] (5) According to 60g / m 2 The obtained composite insulating layer mixed slurry is coated on two positive electrode material active layers and two negative electrode material active layers respectively to form composite electrode active layers, wherein the thickness of the composite insulating layer is 3 μm.

[0107] The thickness ratio of the formed composite insulating layer to the active layer of the negative electrode material is 0.6:1, and the thickness ratio of the formed composite insulating layer to the active layer of the positive electrode material is 0.009:1.

[0108] Comparative Example 1

[0109] The only difference between this comparative example and Example 1 is that no composite insulating layer is prepared. At the same time, when preparing the battery cell sample in this comparative example, the 9+2+2 model of EJ is used as the separator.

[0110] Comparative Example 2

[0111] The only difference between this comparative example and Example 2 is that no composite insulating layer is prepared. At the same time, when preparing the battery cell sample in this comparative example, the 7+3+3 model of EJ is used as the separator.

[0112] Comparative Example 3

[0113] The only difference between this comparative example and Example 3 is that no composite insulating layer is prepared. At the same time, when preparing the battery cell sample in this comparative example, the 12+2 model of EJ is used as the separator.

[0114] Comparative Example 4

[0115] A method for preparing a composite electrode active layer:

[0116] The only difference between this comparative example and Example 3 is that the composite insulating layer does not contain the thermosensitive polymer, and the weight ratio of the inorganic particles to the heat-resistant polymer is changed to 75:25.

[0117] Comparative Example 5

[0118] A method for preparing a composite electrode active layer:

[0119] The only difference between this comparative example and Example 3 is that the composite insulating layer does not contain the heat-resistant polymer, and the weight ratio of the inorganic particles to the heat-sensitive polymer is changed to 75:25.

[0120] Test Method

[0121] Preparation of battery samples: stack the positive electrode sheets and negative electrode sheets obtained in each embodiment and comparative example in order, and then use the stacking to obtain a roll core; place the roll core in a soft-pack outer packaging shell, inject D73 electrolyte at a liquid injection rate of 4.0g / Ah after drying, and obtain a lithium-ion battery sample with a capacity of 1.5Ah after vacuum packaging, standing, formation, and volume separation. For the comparative example without a composite insulating layer, the negative electrode sheet, diaphragm, and positive electrode sheet are stacked to prepare a roll core, and then a battery sample with the same capacity is obtained by the same method as above.

[0122] Performance test of battery samples:

[0123] (1) Discharge capacity retention rate (60°C, 7d): Under a constant temperature environment of 25°C, the obtained secondary battery sample was allowed to stand for 24 hours after formation, and charged to 3.65V at 0.33C constant current and constant voltage, with a cut-off current of 0.05C; then discharged to 2.5V at 0.33C constant current and constant voltage, and the discharge capacity C1 was recorded; then charged to 3.65V at 0.33C constant current and constant voltage, with a cut-off current of 0.05C, and allowed to stand at 60°C for 7d, and then discharged to 2.5V at 0.33C constant current and constant voltage, and the discharge capacity C2 was recorded. The discharge capacity retention rate R = C2 / C1×100%.

[0124] (2) IMP internal resistance: Impedance, i.e. internal resistance. After the above-obtained battery samples were divided into capacities, they were placed in a 25°C environment for 24 hours, and then the IMP1, i.e. the room temperature internal resistance, was tested using a HIOKI voltage internal resistance meter. At the same time, the obtained battery samples were placed in a 120°C constant temperature oven for 30 minutes, and then placed at 25°C for 30 minutes, and the IMP2, i.e. the internal resistance after high temperature storage, was tested using a HIOKI voltage internal resistance meter.

[0125] (3) Safety test: The safety performance of the battery is verified by using a hot box test. In this test, a thermocouple is attached to the surface of the battery and the battery is placed in a hot box. The battery is heated from a starting temperature (25°C) to 180°C at a heating rate of 5±1°C / min and stored for 30 minutes. The temperature of the hot box is required to be 180°C, and then the temperature is kept constant. The changes in battery temperature and voltage over time are recorded, and the time t and temperature T from when the battery is kept constant in the 180°C hot box until a voltage drop occurs are determined.

[0126] The results of the above tests are shown in Table 1.

[0127] Table 1

[0128]

[0129]

[0130] From the above description, it can be seen that the above embodiments of the present invention realize the preparation of a composite electrode active layer that is resistant to high temperatures and has excellent electrical properties, and solve the problem of thermal runaway caused by membrane rupture caused by high temperatures in the field of secondary batteries.

[0131] Specifically, when comparing Examples 1 to 3 with Comparative Examples 1 to 3, the IMP internal resistance of Examples 1 to 3 is greatly improved after hot storage, indicating that the conduction of ions in the liquid phase is hindered, having a good thermosensitive effect, hindering the rapid continued discharge of the battery cell under thermal runaway at 120°C, and having good safety performance; further, in the 180°C thermal shock test, there is no sudden drop in voltage, indicating that no short circuit occurs inside the battery cell, and the safety performance is high; and when Examples 1 to 3 are compared with Comparative Example 4, it is shown that without the addition of the thermosensitive polymer, the battery cell has thermal runaway at 120°C, the internal resistance does not change, and the battery cell will continue to discharge, and the introduction of the thermosensitive polymer can improve the risk of this operating condition; when Examples 1 to 3 are compared with Comparative Example 5, it is shown that when there is no heat-resistant polymer as an adhesive, the thermosensitive polymer melts, and there is still a short circuit between the positive and negative pole pieces.

[0132] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

[0133] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A composite electrode active layer, characterized in that: The composite electrode active layer comprises an active material layer and a composite insulating layer stacked in sequence, wherein the composite insulating layer comprises inorganic particles, a heat-resistant polymer and a thermosensitive polymer; The weight ratio of the inorganic particles, the heat-resistant polymer and the thermosensitive polymer is (50-100): (1-10): (5-50); The melting temperature of the heat-resistant polymer is 180°C to 450°C; The softening temperature of the thermosensitive polymer is 80°C to 120°C.

2. The composite electrode active layer according to claim 1, characterized in that: The weight ratio of the inorganic particles, the heat-resistant polymer and the thermosensitive polymer is (65-85):(3-5):(10-30).

3. The composite electrode active layer according to claim 1 or 2, characterized in that: The heat-resistant polymer is selected from one or more of polyacrylate polymers, polyimide polymers and amide polymers; Preferably, the heat-resistant polymer is selected from one or more of poly(m-phenylene isophthalamide), polyethylene terephthalate and poly(bismaleimide).

4. The composite electrode active layer according to any one of claims 1 to 3, characterized in that: The thermosensitive polymer is selected from one or more of polyol polymers and polyvinyl alcohol polymers; Preferably, the thermosensitive polymer is polyethylene glycol and / or polyvinyl alcohol.

5. The composite electrode active layer according to any one of claims 1 to 4, characterized in that: The D50 of the inorganic particles is 0.1 μm to 6.0 μm, and (D90-D10) / D50 is 0.5 to 3.0; Preferably, the inorganic particles are selected from one or more of boehmite, Al2O3, BaTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, SiO2, Y2O3, SiC and TiO2; More preferably, the inorganic particles are BaTiO3 and TiO2, and the weight ratio of the BaTiO3 to the TiO2 is (0.1-10):

1.

6. The composite electrode active layer according to any one of claims 1 to 5, characterized in that: The thickness of the composite insulating layer is 4 μm to 20 μm; Preferably, the thickness ratio of the composite insulating layer to the active material layer is (0.01-0.5):1; Preferably, the active material layer is a positive electrode material active layer and / or a negative electrode active material layer; More preferably, the positive electrode material is selected from one or more of iron phosphate, manganese iron phosphate and nickel-cobalt-manganese ternary material; and / or, the negative electrode material is selected from one or more of graphite, silicon and silicon-carbon composite materials.

7. The composite electrode active layer according to any one of claims 1 to 6, characterized in that: The inorganic particles are BaTiO3 and TiO2, and the weight ratio of the BaTiO3 to the TiO2 is (0.4-0.5):1; and / or, The heat-resistant polymer is poly(m-phenylene isophthalamide) and polyethylene terephthalate, and the weight ratio of the poly(m-phenylene isophthalamide) to the polyethylene terephthalate is 1:(0.8-1.2); and / or, The thermosensitive polymer is polyethylene glycol and polyvinyl alcohol, and the weight ratio of the polyethylene glycol to the polyvinyl alcohol is 1:(1.8-2.0).

8. An electrode sheet comprising a current collector and an electrode active layer disposed on at least one side surface of the current collector, characterized in that: The electrode active layer is a composite electrode active layer according to any one of claims 1 to 7, and the active material layer in the composite electrode active layer is arranged in contact with the current collector; Preferably, the composite insulating layer is disposed on the surface of the active material layer away from the current collector by a coating process, and the coating surface density of the composite insulating layer during coating is 15 g / m 2 ~45g / m 2 ; The electrode sheet is a negative electrode sheet and / or a positive electrode sheet.

9. The electrode sheet according to claim 8, characterized in that: The electrode sheet is the positive electrode sheet, the current collector is the positive current collector, the active material layer is the positive material active layer, the positive material active layer is arranged on the positive current collector through a coating process, and the coating surface density of the positive material active layer during coating is 100g / m 2 ~400g / m 2 and / or, The electrode sheet is the negative electrode sheet, the current collector is the negative current collector, the active material layer is the negative material active layer, the negative material active layer is arranged on the negative current collector through a coating process, and the coating surface density of the negative material active layer during coating is 40g / m 2 ~200g / m 2 .

10. A secondary battery comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, characterized in that: The positive electrode sheet is the positive electrode sheet according to claim 8 or 9; and / or, the negative electrode sheet is the negative electrode sheet according to claim 8 or 9.

Citation Information

Patent Citations

  • GaN-based light emitting diode and preparation method thereof

    CN101937953A

  • Apparatus and method for measuring the bending angle of a sheet

    CN103381436A

  • Separator for electrochemical device, and electrochemical device

    CN101048892A

  • Battery separator, method for manufacture thereof, and lithium secondary battery

    CN101512792A

  • Lithium ion secondary battery porous multilayer diaphragm and manufacture method thereof

    CN102394282A

Cited By

  • Composite electrode active layer, electrode sheet and secondary battery

    WO2026108011A1